U. S. Spacesuits - Thomas, Kenneth S.; McMann, Harold J. (Space Exploration, 2012)
Spacesuits are far more than garments. They are a personalized spacecraft that allows direct contact and interaction with everything beyond our world, and a last refuge for survival in a disaster. Creating safe, reliable, and comfortable spacesuits is an ongoing challenge that has spanned over four decades. "U. S. Spacesuits, 2nd Edition" by Kenneth S. Thomas and Harold J. McMann details the technical evolution of U. S. spacesuits from their roots in high altitude aviation and vacuum tube development to present day, with an additional look into the future. This primary source of spacesuit information explains the functions, historical development, and use of spacesuits from a worldwide perspective. In this new edition, the authors update the story of U.S. spacesuit development and efforts, from the design challenges modern engineers face to the latest roles of spacesuits in space exploration. The book also provides a close up look at NASA's new Constellation Space Suit System as well as Apollo prototype configurations that have been discovered since 2005. Also not in the earlier edition is a prototype and model of the Gemini pressure suit and an explanation of its development. Finally, there are new insights into the suits used for the Gemini, Apollo, Skylab, Space Shuttle, and International Space Station missions.